Chineseness, situatedness, and what the Thai-Chinese see in Chinese dramas. Issue 1 (2nd January 2023) - Lin, Yi; Nettayakul, Dechawat; Kingminghae, Worapinya
Abstract: Despite their great success in Southeast Asia, Korean dramas have been increasingly facing the challenges of reviving Chinese dramas. Through an online survey, we acquired a sample of 1096 Thai viewers of Chinese dramas and analysed their evaluations primarily from an ethnic perspective. In light of Uses and Gratification Theory, the results indicate that compared with other Thais, the Thai-Chinese attach more importance to the plots and meanings of Chinese dramas while attaching less importance to the fame, looks, and acting of the artists. Based on the findings, we argue that although the recent mainland Chinese dramas can help the Thai-Chinese make sense of their lives, unidirectional re-sinicization is hardly the only way. Rather than relying on cultural proximity and nationalistic sentiments to explain diasporas' homeland cultural consumption, this study emphasizes both the situatedness of the diasporas in the host country and the evolving ways they connect to their homeland.